Transforming Lives and Systems Cultural Competence and the Higher Education Interface - Frawley, Jack; Nguyen, Tran; Sarian, Emma (SpringerBriefs in Education,, 2020)
This open access book explores the transformative experiences of participants in the University of Sydney's National Centre for Cultural Competence (NCCC) programs. The establishment of the NCCC was viewed as a critical point of departure for developing an institution-wide agenda of cultural competence. The NCCC's work since its inception reflects efforts to lay important foundations for cultural change at the University. With the ultimate aim of establishing cultural competence as an agent for transformational change and social justice education, the NCCC has steadily expanded its research and teaching work both within and beyond the University of Sydney. Further, it has developed foundational resources to support and encourage University staff to integrate cultural competence philosophy and pedagogy in their curricula, teaching and research. This includes the ability to engage meaningfully with the cultures, histories and contemporary issues in Aboriginal and Torres Strait Islander communities. The NCCC programs have been designed to encourage participants to learn about who they are and how they can positively impact the transformational change the University has begun. The book presents participants' reflections on their experiences at the organisational and personal level. Readers will gain insights into a range of topics including cultural competence, communities of practice, policy implementation, and transformative leadership at the interface between higher education and professional lives.